Polyethylene-based modifier, recycle resin composition and blow container
By modifying recycled polyethylene with a specific polyethylene modifier, the durability and impact resistance of blow containers are enhanced, addressing the limitations of existing recycled materials in polyethylene-based blow containers.
Patent Information
- Application Number
- JP2024104813
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-28
- Filing Date
- 2024-06-28
- Publication Date
- 2025-01-20
AI Technical Summary
Existing polyethylene-based blow containers made from recycled materials lack sufficient durability, impact resistance, and environmental stress cracking resistance, as current recycling methods do not adequately address the need for high molecular weight components and specific properties.
A polyethylene-based modified material is developed, combining recycled polyethylene with a specific polyethylene modifier to achieve characteristics such as density, melt flow rates, and molecular weight distribution, enhancing tensile strength and impact resistance.
The modified material results in blow containers with improved durability, impact resistance, and reduced plastic waste by utilizing recycled materials effectively.
Smart Images

Figure 2025010031000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyethylene modifier, a recycled resin composition, and a blown container. [Background technology]
[0002] In the field of blown containers, various thermoplastic resins are used. Among them, polyethylene has been extensively studied and is being used because of its excellent mechanical properties, thermal properties, chemical resistance, and the like.
[0003] In recent years, as plastic waste (waste plastic) has become an international problem, efforts to reduce the amount of plastic used and introduce new materials are being considered. Some companies are looking at the raw materials themselves and trying to build new recycling systems. Under these circumstances, even in the field of blown containers made of synthetic resin, consideration is being given to using recycled materials in products.
[0004] For example, Patent Document 1 discloses a polyolefin-based recycled resin composition that is characterized by being composed of a polyolefin-based recycled resin and an ethylene / C3-18 α-olefin copolymer having specific properties produced using a metallocene catalyst. However, from the viewpoint of improving impact resistance and environmental stress crack resistance, the polyolefin-based recycled resin composition does not suggest anything about the amount of essential high molecular weight components, and is not sufficient for modifying the composition for use in blown containers.
[0005] As described in Patent Document 2, [A] (1) may contain less than 10 mol % of units derived from an α-olefin having 3 to 6 carbon atoms, and (2) has a density of 0.92 to 0.98 g / cm 3 (3) an intrinsic viscosity [η] of 0.4 to 10 dl / g; and (4) an ethylene polymer produced using a catalyst containing a metallocene compound represented by a specific structural formula; and [B] a resin composition for blow molding comprising the high-density polyethylene for blow molding other than the high-density polyethylene [A]. However, the modifiers have a wide range of physical properties, and therefore cannot be said to be sufficient for providing durable blown containers by modifying recycled materials.
[0006] On the other hand, as for polyethylene resins, for example, as shown in Patent Document 3, a polyethylene resin containing 10 to 40 mass% of a specific polyethylene component (A), 5 to 50 mass% of a specific polyethylene component (B), and 40 to 85 mass% of a specific polyethylene component (C) has the following properties: characteristic (1): MFR is 0.1 to 1 g / 10 min; characteristic (2): HLMFR is 10 to 50 g / 10 min; characteristic (3): HLMFR / MFR is 50 to 140; and characteristic (4): density is 0.940 to 0.965 g / cm 3 A polyethylene resin composition is disclosed that satisfies the following characteristic: Property (5): an inflection point of the extensional viscosity due to strain hardening is observed in a log-log plot of the extensional viscosity η(t) (unit: Pa·sec) measured at a temperature of 170°C and an extensional strain rate of 0.1 (unit: 1 / sec) versus the extension time t (unit: seconds). It is also disclosed that molded articles can be produced by various molding methods such as blow molding, injection molding, inflation molding, and extrusion molding, but no suggestion is made about application to the field of recycled materials.
[0007] Also, for example, Patent Document 4 discloses a polyethylene resin composition and a modifier in which component (A) and component (B) having specific properties are ethylene-α-olefin copolymers polymerized with a metallocene catalyst, and are polymerized in multiple stages in this order, and which are characterized by satisfying specific properties such as (i) density and (ii) HLMFR. However, there is no suggestion whatsoever about specific recycled materials and their application in fields of use. Furthermore, for example, Patent Document 5 discloses a method for producing a recycled resin composition by mixing a recycled polyolefin resin and a resin composition containing a metallocene-based polyethylene. In particular, the resin composition containing the metallocene-based polyethylene has a density of 0.940 to 0.970 g / cm. 3MFR is 0.1 to 10 g / 10 min, HLMFR is 10 to 100 g / 10 min, HLMFR / MFR is 40 to 140, and tensile impact strength is 300 kJ / m 2 A resin composition having the above characteristics is disclosed. However, the resin composition (B) containing metallocene-based polyethylene used in the examples has a small amount of high molecular weight components, so it cannot be said to be sufficient for providing a blown container having excellent durability and impact resistance.
[0008] Also, for example, Patent Document 6 discloses a polyethylene resin composition using recycled polyethylene resin (A) and ethylene polymers (B) and (C) containing structural units derived from at least one α-olefin having 4 to 10 carbon atoms. However, it is suggested that the modifier consisting of (B) and (C) has a low viscosity due to its high MFR and contains a low amount of metallocene-based high molecular weight component, and therefore it is not sufficient to provide a blown container with excellent impact resistance, and no suggestion is made about improving durability. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Japanese Patent Application Publication No. 8-127676 [Patent Document 2] Japanese Patent Application Publication No. 9-095571 [Patent Document 3] JP 2017-179256 A [Patent Document 4] Patent No. 6281371 [Patent Document 5] Patent Publication No. 2021-95442 [Patent Document 6] JP 2024-48543 A Summary of the Invention [Problem to be solved by the invention]
[0010] In this situation, it is desirable to use recycled materials in blown products, reduce the amount of plastic used, and solve the problem of plastic waste (waste plastic).
[0011] In view of the problems of the above-mentioned conventional technology, the object of the present invention is to apply recycled materials to blown products in the molding of polyethylene blown containers, thereby reducing the amount of plastic used and resolving the problem of plastic waste (waste plastic). In particular, the object is to provide a durable blown container by modifying recycled materials. [Means for solving the problem]
[0012] As a result of intensive research into solving the above-mentioned problems, the inventors have discovered that by using polyethylene-based recycled materials with specific properties and polyethylene-based modified materials with specific properties in blown containers, the recycled materials can be applied to blown products, thereby reducing the amount of plastic used and resolving the problem of plastic waste (waste plastics). They have also discovered that by modifying the recycled materials, it is possible to provide blown containers with excellent durability (e.g., tensile strength, tensile impact strength, environmental stress crack resistance (bottle ESCR), etc.), and have thus completed the present invention.
[0013] That is, the present invention includes the following aspects. [1] A polyethylene-based modifier for modifying a polyethylene-based recycled material that satisfies the following characteristics (1-1) to (1-2): The polyethylene-based modifier is provided to satisfy the following characteristic (2-1). Property (1-1): The polyethylene-based recycled material has a density of 0.930 to 0.980 g / cm 3 It is. Property (1-2): The polyethylene-based recycled material has a melt flow rate (MFR) of 0.1 to 10.0 g / 10 min measured at a temperature of 190°C and a load of 2.16 kg, and a high load melt flow rate (HLMFR) of 1 to 100 g / 10 min measured at a temperature of 190°C and a load of 21.6 kg. Property (2-1): The polyethylene-based modifier has a molecular weight distribution curve of 10 5 The maximum value of the following components is a, and 10 5 When the maximum value of the above components is represented as b, b / a is 0.90 or more, and preferably 0.90 to 2.50.
[0014] [2] The polyethylene modifier according to [1], wherein the polyethylene modifier has a high load melt flow rate (HLMFR) of 1 to 20 g / 10 min measured at a temperature of 190°C and a load of 21.6 kg.
[0015] [3] The polyethylene-based modifier according to [1] or [2], wherein the polyethylene-based modifier has a melt flow rate (MFR) of 0.05 g / 10 min or less measured at a temperature of 190°C and a load of 2.16 kg.
[0016] [4] The polyethylene-based modifier according to any one of [1] to [3], wherein the polyethylene-based modifier contains 40% by mass or more of a polyethylene component polymerized by a metallocene catalyst, when the total amount of polyethylene contained in the polyethylene-based modifier is 100% by mass.
[0017] [5] A recycled resin composition comprising 1 to 50 mass% of the polyethylene-based modifier according to any one of [1] to [4] above and 99 to 50 mass% of the polyethylene-based recycled material.
[0018] [6] The recycled resin composition according to [5] above, which satisfies the following characteristics (i) to (iii): Property (i): Tensile impact strength is 120 kJ / m 2 That's all. Property (ii): Tensile strength in full notch creep test (FNCT) measured at 3.7 MPa in accordance with ISO 16770 is 16 hours or more. Property (iii): HLMFR is 10 g / 10 min or more.
[0019] [7] A blown container comprising the recycled resin composition according to [5] or [6]. Effect of the Invention
[0020] According to the present invention, in the case of polyethylene-based blown containers, recycled materials are applied to blown products, thereby reducing the amount of plastic used and solving the problem of plastic waste (waste plastic), and by modifying the recycled materials, it is possible to provide blown containers with excellent durability. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a graph showing an example of a differential molecular weight distribution curve of a polyethylene-based modifier measured by gel permeation chromatography (GPC). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] According to the present invention, there is provided a polyethylene-based modifier for modifying a polyethylene-based recycled material that satisfies the following characteristics (1-1) to (1-2): The polyethylene-based modifier is provided to satisfy the following characteristic (2-1). Property (1-1): The polyethylene-based recycled material has a density of 0.930 to 0.980 g / cm 3 It is. Property (1-2): The polyethylene-based recycled material has a melt flow rate (MFR) of 0.1 to 10.0 g / 10 min measured at a temperature of 190°C and a load of 2.16 kg, and a high load melt flow rate (HLMFR) of 1 to 100 g / 10 min measured at a temperature of 190°C and a load of 21.6 kg. Property (2-1): The polyethylene-based modifier has a molecular weight distribution curve of 10 5 The maximum value of the following components is a, and 10 5 When the maximum value of the above components is b, b / a is 0.90 or more.
[0023] The present invention will be described in detail below for each item. In the present invention, the polyethylene resin is a general term for ethylene homopolymers and copolymers of ethylene and the olefins described below, and may also be referred to as ethylene polymers. In addition, in this specification, the use of "to" indicating a numerical range means that the numerical values before and after it are included as the lower and upper limits. Furthermore, the upper and lower limits of a numerical range can be in any combination.
[0024] 1. Polyethylene recycled materials In the present invention, polyethylene-based recycled materials (recycled materials) refer to polyethylene-based resins that have been recovered and regenerated after molding and / or use. Specifically, examples of such materials include materials that have been recovered and reused, such as flash, defective products, off-cuts, by-products, etc. that arise during the molding process of polyethylene-based resins, and unused or used molded products after being molded into products, and recycled plastic materials. Polyethylene recycled materials contain carbonyl groups, and when measured by infrared spectroscopy, they meet the following criteria: 4250 and I 1586 With respect to the amount of carbonyl groups contained, the following formula (A) is satisfied. Formula (A): I 1586 / I 4250 ≧0.02 I 4250 In the infrared absorption spectrum, 4600 cm -1 The value of 4250 cm is used as the reference baseline. -1 The difference in height between the peak intensity at and the reference baseline. I 1586 In the infrared absorption spectrum, 1610 cm -1 ~1560cm -1The line connecting these points is the reference baseline, 1586 cm -1 The difference in height between the peak intensity at and the reference baseline. In addition, in this specification, recycled plastic materials mean "materials that are reprocessed from recovered or recycled materials during the manufacturing process and are used in final products or parts that are incorporated into products" in accordance with JIS Q14021:2000. The polyethylene-based recycled material of the present invention contains 60% by mass or more, preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 100% by mass of one or more ethylene-based polymers selected from the group consisting of ethylene homopolymers and copolymers of ethylene and α-olefins having 3 to 12 carbon atoms. In the present invention, the polyethylene-based recycled material can be confirmed by a conventional analytical method to contain an ethylene homopolymer and a copolymer of ethylene and an α-olefin having 3 to 12 carbon atoms, and can also be identified by, for example, measuring a Raman scattering spectrum. In addition, if the polyethylene-based recycled material used in the present invention is commercially available, it is preferable that the commercially available company has quality control and quality certification. In addition, for example, guidelines based on standards conforming to JIS Q9091:2016 can be used as a reference for quality control of plastic recycled materials. Specific examples of polyethylene-based recycled materials include HDPE "HA" manufactured by Mie Kasei Co., Ltd., but there are no particular limitations as long as they satisfy the requirements of the characteristics of the present invention. Since polyethylene-based recycled materials often have inferior physical properties compared to virgin materials, it is important that the blown container of the present invention is able to minimize the deterioration of physical properties and exhibit physical properties equal to or greater than those of virgin materials. It is important that the polyethylene-based recycled material of the present invention satisfies at least the following properties (1-1) and (1-2).
[0025] Characteristics of polyethylene recycled materials (1-1) Characteristics (1-1): Polyethylene recycled materials have a density of 0.930 to 0.980 g / cm 3 It is. In the present invention, the polyethylene-based recycled material has a density of 0.930 to 0.980 g / cm 3 and preferably 0.940 to 0.970 g / cm 3 and more preferably 0.945 to 0.960 g / cm 3 It is important to select materials with a density of 0.930g / cm3 for polyethylene recycled materials. 3 If the density is less than 0.980 g / cm, the polyethylene recycled material will lack rigidity and the crystallization rate will decrease, which may result in a shortened molding cycle. 3 If the density exceeds this range, the impact resistance of the molded product may decrease. Also, if the density is within the above range, the mixability of the polyethylene recycled material with the polyethylene modifier described below is good. The density can be measured in accordance with JIS K6922-1,2:1997.
[0026] Characteristics of polyethylene recycled materials (1-2) Property (1-2): Polyethylene-based recycled materials have a melt flow rate (MFR) of 0.1 to 10.0 g / 10 min. measured at a temperature of 190°C and a load of 2.16 kg, and a high load melt flow rate (HLMFR) of 1 to 100 g / 10 min. measured at a temperature of 190°C and a load of 21.6 kg. In the present invention, it is important to select a polyethylene-based recycled material having a melt flow rate (MFR) of 0.1 to 10.0 g / 10 min, preferably 0.15 to 8.0 g / 10 min, more preferably 0.3 to 7.0 g / 10 min, and even more preferably 1.0 to 5.0 g / 10 min, measured at a temperature of 190 ° C. and a load of 2.16 kg. If the MFR of the polyethylene-based recycled material is less than 0.1 g / 10 min, the fluidity of the polyethylene-based recycled material decreases, which may increase the amount of resin heat generated by the extruder motor load and shear during molding, or may cause flow instability such as shark skin and melt fracture, which may impair the appearance of the molded product. On the other hand, if the MFR exceeds 10.0 g / 10 min, the impact resistance of the molded product may not be achieved, and the long-term durability of the molded product may decrease. In addition, if the MFR is within the above range, the mixability of the polyethylene-based recycled material with the polyethylene-based modifier described later is good. The MFR can be measured in accordance with JIS K6922-2:1997.
[0027] In the present invention, it is important to select a polyethylene-based recycled material having a high load melt flow rate (HLMFR) measured at a temperature of 190°C under a load of 21.6 kg of 1 to 100 g / 10 min, preferably 10 to 80 g / 10 min, more preferably 15 to 60 g / 10 min, and even more preferably 20 to 55 g / 10 min. If the HLMFR of the polyethylene-based recycled material is less than 1 g / 10 min, the fluidity of the polyethylene-based recycled material will decrease, which may increase the amount of heat generated by the resin due to the load on the extruder motor or shear during molding, and may cause flow instability such as sharkskin and melt fracture, which may impair the appearance of the molded product. On the other hand, if the HLMFR exceeds 100 g / 10 min, the impact resistance of the molded product may not be achieved, and the long-term durability of the molded product may decrease. In addition, if the HLMFR is within the above range, the mixability of the polyethylene-based recycled material with the polyethylene-based modifier described later will be good. The HLMFR can be measured in accordance with JIS K6922-2:1997.
[0028] Characteristics of polyethylene recycled materials (1-3) In the present invention, the polyethylene-based recycled material may be selected from those having a ratio of HLMFR to MFR (HLMFR / MFR) of 40 to 140, preferably 50 to 110, and more preferably 60 to 90. HLMFR / MFR is highly correlated with molecular weight distribution, and when HLMFR / MFR is large, the molecular weight distribution becomes wide, and when HLMFR / MFR is small, the molecular weight distribution becomes narrow. If HLMFR / MFR exceeds 140, the pinch-off strength of the bottle molded product may decrease, and if HLMFR / MFR is less than 40, the melt tension of the bottle molded product may decrease or melt fracture may easily occur during resin extrusion. In addition, if HLMFR / MFR is within the above range, the mixability of the polyethylene-based recycled material with the polyethylene-based modifier described later is good.
[0029] Characteristics of polyethylene recycled materials (1-4) In the present invention, the polyethylene-based recycled material may have an environmental stress crack resistance (bottle ESCR) of less than 1000 hours. As described above, polyethylene-based recycled materials usually have lower physical properties than virgin materials, and the polyethylene-based recycled material of the present invention may have an environmental stress crack resistance of at least 1 hour, preferably at least 10 hours, and more preferably at least 100 hours, and less than 1000 hours at the upper limit. In the present invention, by combining a specific polyethylene-based modifier, it is possible to exhibit environmental stress crack resistance equal to or greater than that of a container molded using a virgin material. Environmental stress crack resistance was evaluated by filling a blow-molded flat container (bottle) with an internal volume of 400 ml and a weight of 30 g with 100 ml of an aqueous solution in which a nonionic surfactant (Sigma-Aldrich: polyoxyethylene (9) nonylphenyl ether, Igepearl CO-630) was diluted to 33.3% by volume, and applying a pressure of 0.35 kg / cm 2The bottle ESCR value can be calculated by pressurizing the container to 100 psi, storing it in a thermostatic chamber at 60°C, and measuring the time until the container breaks. This measurement is performed on 10 identical containers, and the time when 5 or more of the 10 containers break is the bottle ESCR value.
[0030] Characteristics of polyethylene recycled materials (1-5) In the present invention, the polyethylene-based recycled material usually has a tensile impact strength of 300 kJ / m 2 Less than 130kJ / m 2 Polyethylene recycled materials usually have lower physical properties than virgin materials, and the polyethylene recycled material of the present invention has a tensile impact strength of 10 kJ / m or less. 2 More than 20 kJ / m 2 or more, with an upper limit of 300 kJ / m 2 Less than or equal to 150 kJ / m 2 In the present invention, by combining a specific polyethylene-based modifier, it is possible to achieve impact resistance equal to or greater than that of a container molded using a virgin material. The tensile impact strength can be measured by preparing a 1.5 mm compression molded sheet in accordance with JIS K6922-2, punching out a test piece with an S-shaped dumbbell in accordance with ASTM D1822, and measuring the strength under conditions of 23°C and 50% RH. The lower limit of the full notch creep test (FNCT) of polyethylene-based recycled materials measured at 3.7 MPa in accordance with ISO 16770 is preferably 0.01 hours or more, more preferably 0.5 hours or more, further preferably 1.0 hour or more, and preferably 1.5 hours or more. The upper limit is preferably as high as possible, and may be, for example, 10 hours or more.
[0031] Characteristics of polyethylene recycled materials (1-6) In the present invention, the polyethylene recycled material preferably contains 10 parts by weight or less of additives relative to 100 parts by weight of the polyethylene recycled material, preferably 5 parts by weight or less, and more preferably 3 parts by weight or less. In the present invention, the additives include known additives such as ordinary olefin polymers, rubbers, antioxidants, ultraviolet absorbers, light stabilizers, lubricants, antistatic agents, antifogging agents, antiblocking agents, processing aids, coloring pigments, crosslinking agents, foaming agents, inorganic or organic fillers, and flame retardants, and examples of such additives include antioxidants (phenolic, phosphorus, sulfuric), lubricants, antistatic agents, light stabilizers, and ultraviolet absorbers. Examples of the filler include calcium carbonate, talc, metal powder (aluminum, copper, iron, lead, etc.), silica stone, diatomaceous earth, alumina, gypsum, mica, clay, asbestos, graphite, carbon black, titanium oxide, and the like. In the present invention, if the content of the additive exceeds 10 parts by weight, the durability of the blown container tends to decrease. In the present invention, the type and content of the additives can be analyzed by a conventional analytical method.
[0032] Characteristics of polyethylene recycled materials (1-7) In the present invention, the polyethylene-based recycled material preferably has a carbonyl group content of less than 5.0 mass% resulting from a maleic anhydride-containing compound, and more preferably does not contain any carbonyl group. The carbonyl group content in the polyethylene-based recycled material can be measured by infrared absorption spectroscopy, and is expressed as a carbonyl group content of 1710 cm -1 and 1790cm -1 It is preferable that no absorption peak is observed in the range of 100 to 2000 nm. If a carbonyl group originating from a maleic anhydride-containing compound is present, this may lead to the generation of gels or the like in the molded product, which is undesirable. In order to prevent polyethylene-based recycled materials from containing carbonyl groups resulting from maleic anhydride-containing compounds, it is important that the polyethylene-based recycled materials are quality-controlled and certified so as to not contain carbonyl groups.
[0033] 2. Polyethylene-based modifier The polyethylene modifier of the present invention may be a mixture of two or more types of polyethylene. The polyethylene modifier of the present invention does not mean a recycled material, but a normal virgin material. That is, in the present invention, the polyethylene modifier does not mean a resin that has been recovered and regenerated after molding and / or use, and if it is a recycled material, this is clearly stated. It is important that the polyethylene modifier of the present invention satisfies at least the following property (2-1).
[0034] Characteristics of polyethylene-based modified materials (2-1) Characteristics (2-1): The polyethylene-based modifier is a 10 5 The maximum value of the following components is a, and 10 5 When the maximum value of the above components is b, b / a is 0.90 or more. In the present invention, the polyethylene-based modifier is a polyethylene-equivalent mass modifier having a molecular weight distribution curve of 10 5 The maximum value of the following components is a, and 10 5 When the maximum value of the above components is b, it is important to select one in which b / a is 0.90 or more, preferably 0.90 to 2.50, preferably 0.95 to 1.80, more preferably 1.00 to 1.65, and even more preferably 1.10 to 1.50. The molecular weight distribution (Mw / Mn) measured by GPC is related to the improvement of various physical properties and moldability of the polymer, and also to the improvement of the appearance of the molded article. If the b / a of the polyethylene-based modifier is less than 0.90, the rigidity of the polyethylene-based modifier is insufficient and the crystallization rate is reduced, which may result in a reduction in the molding cycle of the molded article. The molecular weight distribution can be controlled within a desired range by using a catalyst capable of controlling the molecular weight distribution or by using appropriate polymerization conditions. In the case of a bimodal or multimodal polymer, the molecular weight distribution can be controlled by adjusting the molecular weight of each component. For example, Mw=105 The above ingredients (preferably 5 × 10 5 By increasing the ratio (above) and mixing, b / a increases, and vice versa, b / a can be controlled to decrease. The molecular weight and molecular weight distribution can be measured by gel permeation chromatography (GPC) under the conditions described in JP 2017-179256 A.
[0035] FIG. 1 is a graph showing an example of a differential molecular weight distribution curve of a polyethylene-based modifier measured by gel permeation chromatography (GPC). As shown in Figure 1, the 10 5 The maximum value of the following components is a, and 10 5 Let b be the maximum value of the above components.
[0036] Characteristics of polyethylene-based modified materials (2-2) In the present invention, the polyethylene-based modifier preferably has an HLMFR of 0.5 to 100 g / 10 min, preferably 1.0 to 80 g / 10 min, more preferably 3.0 to 60 g / 10 min, even more preferably 4.0 to 40 g / 10 min, and still more preferably 4.3 to 20 g / 10 min. If the HLMFR is less than 0.5 g / 10 min, the fluidity of the polyethylene-based modifier is reduced, which may increase the amount of heat generated by the resin due to the load on the extruder motor or shear during molding, or may cause flow instability such as sharkskin or melt fracture, which may impair the appearance of the molded product, or may make it impossible to pelletize and commercialize the product. On the other hand, if the HLMFR exceeds 100 g / 10 min, the impact resistance of the molded product may not be achieved, and the long-term durability of the molded product may be reduced. In addition, if the HLMFR is within the above range, the mixability of the polyethylene-based recycled material and the polyethylene-based modifier is good. The upper limit of the melt flow rate (MFR) of the polyethylene-based modifier measured at a temperature of 190° C. and a load of 2.16 kg is preferably 0.05 g / 10 min or less, more preferably 0.04 g / 10 min or less, particularly preferably 0.03 g / 10 min or less, more preferably 0.02 g / 10 min or less, and particularly preferably 0.01 g / 10 min or less. The lower limit of the MFR is preferably 0.001 g / 10 min or more in terms of reducing production costs. The HLMFR and MFR of the polyethylene modifier can be adjusted by the amount of hydrogen and temperature during polymerization of each of the components constituting the polyethylene modifier, as well as the blending ratio of the components constituting the polyethylene modifier.
[0037] Characteristics of polyethylene-based modified materials (2-3) In the present invention, the polyethylene-based modifier preferably has a density of 0.910 to 0.970 g / cm 3 and more preferably 0.920 to 0.970 g / cm 3 and more preferably 0.925 to 0.965 g / cm 3 and more preferably 0.930 to 0.960 g / cm 3 and even more preferably 0.935 to 0.958 g / cm 3 The density of the polyethylene modifier is 0.910g / cm 3 If the density is less than 0.970 g / cm, the rigidity of the polyethylene modifier is insufficient and the crystallization rate is reduced, which may result in a reduction in the molding cycle of the molded product. 3 If the density exceeds this range, the durability of the molded product may decrease. Also, if the density is within the above range, the polyethylene recycled material and the polyethylene modifier can be mixed well. The density can be measured in accordance with JIS K6922-1,2:1997. The density can be adjusted by the amount of α-olefin used during polymerization of the components constituting the polyethylene resin, and can also be adjusted by the blending ratio of the components constituting the polyethylene resin.
[0038] Properties of polyethylene-based modified materials (2-4) In the present invention, the polyethylene-based modifier preferably has a tensile impact strength of 300 kJ / m 2 More preferably, 600 kJ / m 2 More preferably, 900 kJ / m 2 The upper limit of the tensile impact strength of the polyethylene-based modifier is not particularly limited, but is generally 2000 kJ / m 2 The following is the norm. It is difficult for Ziegler-based polyethylene resin alone or chromium-based polyethylene resin alone to exhibit the high tensile impact strength of polyethylene-based modified materials. Tensile impact strength of 300 kJ / m 2 By using the above resin, the tensile impact strength of the composition with the polyethylene-based recycled material can be increased. The tensile impact strength can be measured by preparing a 1.5 mm compression molded sheet in accordance with JIS K6922-2, punching out a test piece with an S-shaped dumbbell in accordance with ASTM D1822, and measuring the strength under conditions of 23°C and 50% RH.
[0039] Properties of polyethylene-based modified materials (2-5) The polyethylene modifier preferably contains 40% by mass or more of polyethylene components polymerized by a metallocene catalyst when the total amount of polyethylene contained in the polyethylene modifier is taken as 100% by mass. The reason why it is better to increase this ratio is considered as follows. When polymerization is performed using a nonmetallocene catalyst, the active points of the catalyst are nonuniform, so polymers with unintended molecular weights are also produced by polymerization, and the polymer has a wide molecular weight distribution, but when polymerization is performed using a metallocene catalyst, the active points of the catalyst are uniform, so the polymer has a narrow distribution in the high molecular weight range required from the perspective of impact resistance and long-term performance. Another feature of the metallocene catalyst is that the comonomer is introduced uniformly, which makes it easier to promote the production of tie molecules required for long-term performance. The polyethylene modifier used in the present invention may be a mixture of two or more polyethylenes as long as it satisfies the above-mentioned characteristics, and specifically, the one described in JP 2017-179256 A can be used. As the resin composition, a resin composition containing a polyethylene component polymerized by a metallocene catalyst and at least one polyethylene component (a polyethylene component polymerized by a catalyst other than a metallocene catalyst) among a polyethylene component polymerized by a chromium catalyst and a polyethylene component polymerized by a Ziegler catalyst is preferable. The polyethylene modifier is preferably a resin composition containing 40% by mass, preferably 45 to 99% by mass, more preferably 50 to 80% by mass, and even more preferably 60 to 70% by mass of a polyethylene component polymerized by a metallocene catalyst. As the above metallocene catalyst, chromium catalyst, and Ziegler catalyst, a commonly known polymerization catalyst can be used, and preferably, the polymerization catalyst described in JP 2017-179256 A can be mentioned.
[0040] Characteristics of polyethylene components polymerized with metallocene catalysts (2-5-1) In the polyethylene-based modifier, the polyethylene component polymerized by the metallocene catalyst has a high load melt flow rate (HLMFR) of 0.2 g / 10 min or more and less than 5 g / 10 min, preferably 0.3 to 2.0 g / 10 min, and more preferably 0.6 to 1.5 g / 10 min, at a temperature of 190° C. and a load of 21.6 kg. If the HLMFR is less than 0.2 g / 10 min, the HLMFR in the final resin composition cannot be achieved within the specified range, and there is a risk of reduced fluidity and reduced compatibility, which may impair the appearance of the molded product. On the other hand, if the HLMFR is 5 g / 10 min or more, there is a risk of reduced long-term durability of the molded product in the final resin composition. The HLMFR can be adjusted mainly by the amount of hydrogen and the polymerization temperature during polymerization of the polyethylene component. As a characteristic of the molecular weight distribution of the polyethylene component polymerized by the metallocene catalyst, the Mw (weight average molecular weight) measured by GPC is preferably 1.0×10 5 ~5.0×10 5and more preferably 2.0×10 5 ~4.0×10 5 and more preferably 2.5×10 5 ~3.5×10 5 It is.
[0041] In the polyethylene-based modifier, the polyethylene component polymerized by a metallocene catalyst preferably has a density of 0.915 to 0.945 g / cm 3 , more preferably 0.920 to 0.935 g / cm 3 The density is 0.915g / cm 3 If the density is less than 0.945 g / cm, the density range in the final resin composition cannot be achieved, the rigidity is insufficient, and the crystallization rate is reduced, which may result in a reduced molding cycle. 3 If the density exceeds this range, the durability of the final resin composition may decrease. The density can be adjusted mainly by the amount of α-olefin used during polymerization of the polyethylene component.
[0042] Characteristics of polyethylene components polymerized with chromium catalysts (2-5-2) In the polyethylene-based modifier, the polyethylene component polymerized by a chromium-based catalyst preferably has an HLMFR of 2 g / 10 min or more and less than 20 g / 10 min, more preferably 3 to 15 g / 10 min, even more preferably 4 to 12 g / 10 min, and particularly preferably 5 to 10 g / 10 min. If the HLMFR is less than 2 g / 10 min, the molecular weight increases, and fluidity and moldability may not be ensured. In addition, in the final resin composition, the HLMFR may not be within the specified range, and fluidity may decrease, or the polyethylene component may become the component with the highest viscosity in the low strain rate range, resulting in poor dispersion of the polyethylene component and impairing the appearance of the molded product. On the other hand, if the HLMFR is 20 g / 10 min or more, the amount of low molecular weight components increases, and impact resistance may not be ensured, or the dispersion promotion effect of each component may decrease. The HLMFR can be adjusted mainly by the amount of hydrogen and polymerization temperature during polymerization of the polyethylene component.
[0043] In the polyethylene-based modifier, the polyethylene component polymerized by a chromium-based catalyst preferably has a density of 0.945 g / cm 3 Excess, 0.965g / cm 3 or less, more preferably 0.950 to 0.963 g / cm 3 , more preferably 0.956 to 0.961 g / cm 3 The density of the polyethylene component is 0.945 g / cm 3 If the density is less than 0.965 g / cm, the density range of the final resin composition cannot be achieved, the rigidity is insufficient, and the crystallization rate is reduced, which may result in a reduced molding cycle. In addition, the rigidity of the container is poor and it is prone to deformation at high temperatures, and the container may be deformed due to the influence of the internal pressure of the container, which may cause leakage. On the other hand, if the density is less than 0.965 g / cm, the density range of the final resin composition cannot be achieved, the rigidity is insufficient, and the crystallization rate is reduced, which may result in a reduced molding cycle. In addition, the rigidity of the container is poor and it is prone to deformation at high temperatures, and the container may be deformed due to the influence of the internal pressure of the container, which may cause leakage. 3 If the density exceeds 100%, the impact resistance of the final resin composition may decrease, and the impact resistance of the container may be poor. The density can be adjusted mainly by the amount of α-olefin used during polymerization of the polyethylene component.
[0044] Properties of polyethylene components polymerized with Ziegler catalyst (2-5-3) In the polyethylene-based modifier, the polyethylene component polymerized by the Ziegler catalyst has a melt flow rate (MFR) at a temperature of 190°C and a load of 2.16 kg of preferably 1 to 200 g / 10 min, more preferably 2.5 to 198 g / 10 min, more preferably 10 to 188 g / 10 min, and even more preferably 20 to 188 g / 10 min. If the MFR is less than 1 g / 10 min, the molecular weight increases, and fluidity and moldability may not be ensured. In addition, in the final resin composition, the HLMFR cannot be achieved within the specified range, and the fluidity decreases, which makes it easy for flow instability phenomena such as sharkskin and melt fracture to occur, and the appearance of the molded product may be impaired. On the other hand, if the MFR exceeds 200 g / 10 min, the impact resistance may not be ensured due to the influence of an increase in the amount of low molecular weight components. In addition, in the final resin composition, the impact resistance may not be achieved, and the durability of the molded product may decrease. The MFR can be adjusted mainly by the amount of hydrogen and the polymerization temperature during polymerization of the polyethylene component.
[0045] In the polyethylene-based modifier, the polyethylene component polymerized by a Ziegler catalyst preferably has a density of 0.960 to 0.980 g / cm 3 , more preferably 0.961 to 0.975 g / cm 3 , more preferably 0.963 to 0.968 g / cm 3 The density is 0.960g / cm 3 If the density is less than 0.980 g / cm, the density range of the final resin composition cannot be achieved, the rigidity is insufficient, and the crystallization rate is reduced, which may result in a reduced molding cycle. In addition, the rigidity of the container is poor and it is easily deformed at high temperatures, and the container may be deformed due to the influence of the internal pressure of the container, which may cause leakage. 3 If the density exceeds 100%, the impact resistance of the final resin composition may decrease, and the durability of the container may decrease. The density can be adjusted mainly by the amount of α-olefin used during polymerization of the polyethylene component.
[0046] The ethylene used in the polyethylene component of the polyethylene-based modifier of the present invention may be ethylene produced from crude oil derived from normal fossil raw materials, or may be plant-derived ethylene. Examples of plant-derived ethylene and polyethylene include ethylene and its polymers described in JP-A-2010-511634. Plant-derived ethylene and its polymers are carbon-neutral (do not use fossil raw materials and do not lead to an increase in carbon dioxide in the atmosphere), making it possible to provide environmentally friendly products.
[0047] 3. Recycled resin composition The recycled resin composition of the present invention contains 99 to 50 mass %, preferably 95 to 51 mass %, more preferably 90 to 52 mass %, and even more preferably 85 to 53 mass % of a polyethylene-based recycled material satisfying at least the above-mentioned properties (1-1) and (1-2), and 1 to 50 mass %, preferably 5 to 49 mass %, more preferably 10 to 48 mass %, and even more preferably 15 to 47 mass % of a polyethylene-based modifier satisfying at least the above-mentioned property (2-1). The recycled resin composition of the present invention contains 50% by mass or more of a polyethylene-based recycled material, and by containing 50% by mass or more of a polyethylene-based recycled material, it is possible to reduce the amount of plastic used. The recycled resin composition may satisfy at least the following characteristics (i) to (iii).
[0048] Characteristics of recycled resin composition (i) Property (i): Tensile impact strength is 120 kJ / m 2 That's all. In the present invention, the recycled resin composition preferably has a tensile impact strength of 120 KJ / m 2 More preferably, 130KJ / m 2 More preferably, it is 150KJ / m or more. 2 Tensile impact strength is 120KJ / m or more. 2If the modifier is less than this, the impact resistance of the blown container tends to decrease. The tensile impact strength can be increased by increasing the composition ratio of the polyethylene modifier.
[0049] Characteristics of recycled resin composition (ii) Property (ii): Tensile strength in full notch creep test (FNCT) measured at 3.7 MPa in accordance with ISO 16770 is 16 hours or more. In the present invention, the recycled resin composition has a tensile strength of preferably 16 hours or more, more preferably 30 hours or more, and even more preferably 40 hours or more, as determined by a full notch creep test (FNCT) measured at 3.7 MPa in accordance with ISO 16770.
[0050] Characteristics of recycled resin composition (iii) Property (iii): HLMFR is 10 g / 10 min or more. In the present invention, the recycled resin composition has a high load melt flow rate (HLMFR) of 10 g / 10 min or more at a temperature of 190° C. and a load of 21.6 kg, and the HLMFR is preferably 13 to 100 g / 10 min, 15 to 45 g / 10 min, 16 to 38 g / 10 min, 20 to 35 g / 10 min, or 22 to 30 g / 10 min. If the HLMFR is less than 10 g / 10 min, the fluidity of the recycled resin composition may decrease, which may increase the amount of heat generated by the resin due to the load on the extruder motor or shear during molding, or may cause flow instability such as sharkskin or melt fracture, which may impair the appearance of the molded product. On the other hand, if the HLMFR exceeds 100 g / 10 min, the long-term durability of the molded product may decrease. The HLMFR of the recycled resin composition can be adjusted by the amount of hydrogen and temperature during polymerization of each of the components constituting the polyethylene-based modifier, the blending ratio of the components constituting the polyethylene-based modifier, and the blending ratio of the polyethylene-based modifier and the polyethylene-based recycled material.
[0051] Characteristics of recycled resin compositions (iv) Characteristics (iv): Density is 0.930 to 0.980 g / cm 3 It is. In the present invention, the recycled resin composition has a density of 0.930 to 0.980 g / cm 3 and preferably 0.940 to 0.970 g / cm 3 and more preferably 0.950 to 0.960 g / cm 3 The density of the recycled resin composition is 0.930 g / cm 3 If the density is less than 0.980 g / cm3, the rigidity is insufficient and the crystallization rate is decreased, which may result in a decrease in the molding cycle. 3 If it exceeds this value, the impact resistance may decrease. The density can be adjusted by the amount of α-olefin during polymerization of the components that make up the polyethylene-based modifier, and can also be adjusted by the blending ratio of the components that make up the polyethylene-based modifier, and the blending ratio of the polyethylene-based modifier and the polyethylene-based recycled material.
[0052] Characteristics of recycled resin compositions (v) The recycled resin composition of the present invention preferably has a carbonyl group content of less than 2.5% by mass derived from a maleic anhydride-containing compound, and more preferably does not contain any carbonyl group. The carbonyl group content in the recycled resin composition can be measured by infrared absorption spectroscopy, and is expressed as a value of 1710 cm -1 and 1790cm -1 It is preferable that no absorption peak is observed in the maleic anhydride-containing compound. The presence of a carbonyl group resulting from the maleic anhydride-containing compound is undesirable because it may lead to the generation of gel, etc. In order to ensure that the recycled resin composition does not contain carbonyl groups resulting from maleic anhydride-containing compounds, it is important that the polyethylene-based recycled materials and the like are quality-controlled and certified so as not to contain carbonyl groups.
[0053] The polyethylene-based modifier and the recycled resin composition of the present invention may contain various conventional additives such as antioxidants, neutralizers, ultraviolet absorbers, light stabilizers, lubricants, antistatic agents, antifogging agents, antiblocking agents, processing aids, coloring agents, crosslinking agents, foaming agents, inorganic or organic fillers, flame retardants, etc. The content of the additives is the same as the content that may be contained in the polyethylene-based recycled material.
[0054] 4. Blow container molding method The blown container of the present invention can be molded by a normal blow molding method. Examples of the blow molding method include an extrusion method, an accumulator method, a hot parison method, a cold parison method, and an injection method. For example, the blown container of the present invention can be manufactured by extruding a recycled resin composition from an extruder to produce a molten parison, setting the parison in a mold having a desired container shape of a blow molding machine, blowing compressed gas into it to expand it to the inner wall of the mold, and then cooling it. In addition, examples of the continuous molding mechanism include a shuttle type, a rotary type, and a satellite type, and examples of the mold clamping method include a hydraulic type, an electric type, and a toggle type. In a specific molding method for the blown container of the present invention, the extrusion temperature of the resin is 180 to 240°C, preferably 190 to 230°C, and more preferably 200 to 220°C. The extrusion pressure of the resin is 50 MPa or less, preferably 40 MPa or less, and more preferably 30 MPa or less. The temperature of the blow mold is 5 to 30°C, preferably 10 to 25°C, and more preferably 15 to 20°C. The blow pressure is 0.3 to 0.8 MPa, preferably 0.4 to 0.7 MPa, and more preferably 0.5 to 0.6 MPa.
[0055] 5.Blow container The blown container of the present invention is not particularly limited as long as it is a blown container containing the recycled resin composition of the present invention, and may be a blown container made of the recycled resin composition of the present invention. The blown container of the present invention may be a blow molded product made from the recycled resin composition by a blow molding method, or may be a multi-layer blow molded product made from the recycled resin composition by a multi-layer blow molding machine as necessary. The size of the blow molded product is not particularly limited, but is preferably about 10 ml to 2000 ml. The shape of the container is not particularly limited, but various printings or layers may be provided on the surface of the outer layer of the blown container of the present invention as necessary. The blown container of the present invention may be a hollow container having a shape that is not simply cylindrical but has parts with significantly different blow ratios of the parison within the same molded product, such as a container with a handle, a container having a bellows-like structure, a container with a waist, or a container consisting of a combination of parts with different diameters.
[0056] Normally, even the smallest amount of recycled material used significantly reduces durability, but the blown container of the present invention does not experience a reduction in durability, even though it uses polyethylene-based recycled materials.
[0057] The blown container of the present invention has good uniformity in wall thickness, excellent surface uniformity, and excellent chemical resistance, impact resistance, etc., and is suitable for applications such as containers that require such characteristics, and can be particularly suitably used for applications such as cosmetic containers, containers for detergents, shampoos and conditioners, or containers for foods such as edible oils, where a good appearance is required. Further examples of uses of the blown container of the present invention include medical containers, food containers, cosmetic containers, etc. Food containers include various beverage containers, concentrated beverage containers, seasoning containers, prepared food containers, dressing containers, mayonnaise / ketchup containers, various retort food containers, baby bottles, etc. Cosmetic containers include containers for hair styling products, hair products, perfumes, hair dyes, eye shadow, nail polish, lotions, creams, milky lotions, skin lotions, perm solutions, etc. EXAMPLES
[0058] The present invention will be explained in more detail below by way of examples, but the present invention is not limited to these examples as long as it does not deviate from the gist of the invention.
[0059] 1.Measurement method The measurement methods used in the examples are as follows. (1) Density Measurements were performed in accordance with JIS K6922-1,2:1997. (2) Melt flow rate (MFR) at a temperature of 190°C and a load of 2.16 kg Measurements were performed in accordance with JIS K6922-2:1997. (3) High load melt flow rate (HLMFR) at 190°C and 21.6 kg load Measurements were performed in accordance with JIS K6922-2:1997.
[0060] (4) Tensile impact strength (TIS) The tensile impact strength was measured by preparing a 1.5 mm compression molded sheet in accordance with JIS K6922-2, punching out test pieces with an S-shaped dumbbell in accordance with ASTM D1822, and measuring the strength at 23°C and 50% RH.
[0061] (5) Tensile strength The tensile strength was measured by a full notch creep test (FNCT) in accordance with ISO 16770. A test piece with a cross section of 4 mm x 4 mm was prepared by making a 1 mm notch with a razor blade all around the circumference of a square column measuring 6 mm x 6 mm x 60 mm, and a tensile stress equivalent to 3.7 MPa was applied to the specimen in pure water at 80°C. The time until the specimen broke was measured and recorded as the breakage time of the FNCT. (6) Infrared absorption spectrum measurement The sample was melted at 180° C. for 3 minutes and compression molded to prepare a film with a thickness of about 50 μm. This film was analyzed by Fourier transform infrared spectroscopy to obtain an infrared absorption spectrum. Product name: FT / IR-6100 manufactured by JASCO Corporation Measurement method: transmission method Detector: TGS (Triglycine sulfate) Number of times: 16 to 512 Resolution: 4.0cm -1 Measurement wavelength: 5000~500cm -1
[0062] 2. Raw Materials 2.1 Polyethylene-based recycled materials (1) Polyethylene recycled materials Density 0.960g / cm 3 , MFR was 0.70g / 10min, HLMFR was 55g / 10min, bottle ESCR was 1.4h, FNCT was 1.5h, I 1586 / I 4250 Recycled plastic with a refractive index of 0.022 was used.
[0063] 2.2 Raw materials for polyethylene modifiers (1) Polyethylene component polymerized with a metallocene catalyst (MA) HLMFR is 0.6g / 10min and density is 0.920g / cm 3 , Mw is 3.0×10 5 The polyethylene component used was: (2) Polyethylene component polymerized with a metallocene catalyst (MB) HLMFR is 1.5g / 10min and density is 0.920g / cm 3 , Mw is 2.3 × 10 5 The polyethylene component used was: (3) Polyethylene component polymerized with a chromium catalyst (CA) HLMFR is 5g / 10min and density is 0.956g / cm 3 The polyethylene component used was: (4) Polyethylene component polymerized with a Ziegler catalyst (ZA) MFR 20g / 10min, density 0.963g / cm 3 The polyethylene component used was: (5) Polyethylene component polymerized with a Ziegler catalyst (ZB) MFR 57g / 10min, density 0.967g / cm 3 The polyethylene component used was: (6) Polyethylene component polymerized with a Ziegler catalyst (ZC) MFR 92g / 10min, density 0.968g / cm 3 The polyethylene component used was: (7) Polyethylene component polymerized with a Ziegler catalyst (ZD) MFR is 188g / 10min, density is 0.968g / cm 3 The polyethylene component used was: (8) Polyethylene component polymerized with a Ziegler catalyst (ZE) MFR is 2.5g / 10min, density is 0.965g / cm 3 The polyethylene component used was:
[0064] 3. Examples, Reference Examples and Comparative Examples [Examples 1 to 17, Reference Example 1, Comparative Examples 1 to 5] (1) Polyethylene-based modifier A polyethylene modifier was prepared containing a polyethylene component polymerized by a metallocene catalyst, at least one of a polyethylene component polymerized by a chromium catalyst and a polyethylene component polymerized by a Ziegler catalyst other than a metallocene catalyst, and a phenolic antioxidant, a phosphorus antioxidant, and calcium stearate (neutralizing agent) as additives, in the proportions shown in Tables 1 and 2. Tables 1 and 2 show the parts by weight of each additive when the total amount of polyethylene in the polyethylene modifier is taken as 100 parts by weight. For the polyethylene-based modifiers of each Example, Reference Example 1, and each Comparative Example, the 10 5 The maximum value of the following components is a, and 10 5 The ratio b / a was calculated assuming that the maximum value of the above components is b. The results are shown in Tables 1 and 2. The HLMFR, MFR and density of the polyethylene-based modifiers of each Example, Reference Example 1 and Comparative Example were measured. The results are shown in Tables 1 and 2. The polyethylene modifier of Comparative Example 1 has a composition equivalent to the resin compositions containing metallocene-based polyethylene of Examples 1 to 6 described in Table 1 of Patent Document 5.
[0065] (2) Recycled resin composition Recycled resin compositions of each Example, Reference Example 1, and Comparative Example were prepared containing the polyethylene modifier of each Example and the polyethylene recycled material in the mixing ratio shown in Table 1. For each of the recycled resin compositions of the Examples, Reference Example 1, and Comparative Examples, the HLMFR, density, tensile impact strength (TIS), and tensile strength by full notch creep test (FNCT) were measured. The results are shown in Tables 1 and 2.
[0066] [Table 1]
[0067] [Table 2]
[0068] As shown in Tables 1 and 2, the polyethylene modifiers in each Example had b / a within the range specified by the present invention, and the recycled resin compositions in each Example satisfied the desired conditions for HLMFR, density, tensile impact strength, and tensile strength. On the other hand, as shown in Table 2, the polyethylene-based modifiers in each comparative example had b / a outside the range specified in the present invention, and the recycled resin compositions in each comparative example did not satisfy the desired conditions for at least tensile strength among the HLMFR, density, tensile impact strength, and tensile strength. [Industrial Applicability]
[0069] According to the present invention, by using polyethylene-based recycled materials with specific properties and polyethylene-based modified materials with specific properties in polyethylene-based blown containers, the recycled materials can be applied to blown products, thereby reducing the amount of plastic used and solving the problem of plastic waste (waste plastic), and by modifying the recycled materials, blown containers with excellent durability can be provided, which is of great industrial utility. In particular, the present invention enables efficient use of recycled materials, making it possible to build a recycling-based economic system from the standpoint of saving resources and solving global environmental problems, and is therefore of great industrial value.
Claims
1. A polyethylene-based modifier for modifying a polyethylene-based recycled material that satisfies the following characteristics (1-1) to (1-2): The polyethylene-based modifier satisfies the following characteristic (2-1): Property (1-1): The polyethylene-based recycled material has a density of 0.930 to 0.980 g / cm 3 It is. Property (1-2): The polyethylene-based recycled material has a melt flow rate (MFR) of 0.1 to 10.0 g / 10 min measured at a temperature of 190° C. and a load of 2.16 kg, and a high load melt flow rate (HLMFR) of 1 to 100 g / 10 min measured at a temperature of 190° C. and a load of 21.6 kg. Property (2-1): The polyethylene-based modifier has a molecular weight distribution curve of 10 5 The maximum value of the following components is a, and 10 5 When the maximum value of the above components is represented as b, b / a is 0.90 or more.
2. The polyethylene-based modifier according to claim 1, wherein the polyethylene-based modifier has a high load melt flow rate (HLMFR) of 1 to 20 g / 10 min measured at a temperature of 190 ° C. and a load of 21.6 kg.
3. The polyethylene-based modifier according to claim 1 or 2, wherein the polyethylene-based modifier has a melt flow rate (MFR) of 0.05 g / 10 min or less measured at a temperature of 190° C. and a load of 2.16 kg.
4. The polyethylene-based modifier contains 40% by mass or more of a polyethylene component polymerized by a metallocene catalyst when the total amount of polyethylene contained in the polyethylene-based modifier is 100% by mass. The polyethylene-based modifier according to claim 1 or 2.
5. The recycled resin composition according to claim 1, comprising 1 to 50% by mass of the polyethylene-based modifier and 99 to 50% by mass of the polyethylene-based recycled material.
6. The recycled resin composition according to claim 5, which satisfies the following characteristics (i) to (iii): Property (i): Tensile impact strength of 120 kJ / m 2 That's all. Property (ii): Tensile strength according to full notch creep test (FNCT) measured at 3.7 MPa in accordance with ISO 16770 is 16 hours or more. Property (iii): HLMFR is 10 g / 10 min or more.
7. A blown container comprising the recycled resin composition according to claim 5 or 6.
Citation Information
Patent Citations
Novel acridine derivative
JP1987081371A
Recycled polyolefin resin composition
JP1996127676A
Modifier for high-density polyethylene and resin composition for blow molding
JP1997095571A
Polyethylene resin composition, molded body thereof and container
JP2017179256A
Recyclable resin composition and blow container
JP2021095442A